2018
DOI: 10.1016/j.precisioneng.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic structures on 316L stainless steel surfaces machined by nanosecond pulsed laser

Abstract: In this paper nanosecond laser machining process was developed to improve the hydrophobicity of AISI 316L stainless steel surface. A geometrical model of laser machined Gaussian micro hole, together with constrain conditions, was established for the first time to predict surface contact angle and optimize structure geometries for maximizing its hydrophobicity. The effects of processing laser power and pitch of microstructures on the topography of the machined surface were investigated through laser machining e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 32 publications
3
70
0
Order By: Relevance
“…The dual-scale roughness of many superhydrophobic surfaces can be exploited to generate bulkier protective features (Figure 10) [93,80]. The principle behind this approach is to utilise larger, more resilience morphological features to act as the sacrificial points of contact when handled manually.…”
Section: Protective Surface Featuresmentioning
confidence: 99%
“…The dual-scale roughness of many superhydrophobic surfaces can be exploited to generate bulkier protective features (Figure 10) [93,80]. The principle behind this approach is to utilise larger, more resilience morphological features to act as the sacrificial points of contact when handled manually.…”
Section: Protective Surface Featuresmentioning
confidence: 99%
“…Periodic black silicon antireflection surface structures were fabricated using four-beam laser interference lithography and studied [25]. In general, nanosecond pulsed lasers have proved to be a reliable tool for achieving ultralow reflectance due to their high processing efficiency and low cost [26,27]. Boinocivh et al used a nanosecond laser to induce regular microgrooves by covering titanium alloy surfaces with porous nanostructures, and the modified surfaces were superior in terms of both corrosion and wear resistance [28].…”
Section: Of 11mentioning
confidence: 99%
“…Superhydrophobic surfaces were the surfaces with a water contact angle (CA) above 150 • and a contact angle hysteresis below 5 • . Materials with superhydrophobic surface show great potential, and have been widely applied in the field of biomedical materials, especially for cardiovascular stent materials, due to their unique characteristics, such as self-cleaning, low adhesion and reduced viscosity resistance [6][7][8][9][10]. For instance, it has been reported that superhydrophobic surfaces could hinder the adhesion of bacteria to surface so as to reduce the risk of instrument and implant infections [11].…”
Section: Introductionmentioning
confidence: 99%